Use of levosimendan in acute heart failure: readmissions, mortality and impact on NT-proBNP. (2nd May 2022) - Silva, G; Silva, M; Caeiro, D; Queiros, P; Ferreira, D; Brandao, M; Fontes-Carvalho, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Acute heart failure (AHF) is a complex clinical condition associated with high morbidity and mortality. Treatment of AHF remains a therapeutic challenge, with inotropic agents playing an important role. Levosimendan (LVS) is distinguished from other catecholaminergic inotropic by its three mechanisms of action - inotropic, vasodilator and cardioprotection - and by the presence of a long-acting metabolite. Objective: We aimed to characterize the predictors of mortality and readmission rate following AHF hospitalizations treated with LVS. Methods and Results: This is a retrospective analysis of all 69 patients treated with LVS in a Cardiology Department at a Tertiary Center (84% male, mean age 65 ± 13 years and mean left ventricular ejection fraction 27 ± 12%). 30-day and 6-month mortality was 23.2% and 36.2%, respectively. Risk factors for 30-day mortality (p <0.05) were: obesity (41% vs 17%), absence of valvular heart disease (48% vs 13%) and plasma creatinine (pCr) variation after LVS infusion (+0.05 mg/dL vs -0.24 mg/dL). Patients with ischemic heart disease have higher mortality at 6 months (68% vs 25%, p=0.001). Risk factors for both 30-day and 6-month mortality (p<0.05) were: chronic kidney disease stage ≥3 (40% vs 10%; 63% vs 15%), pCr before LSV (1.97 vs 1.43mg/dL; 1.83 vs 1.48mg/dL) and pCr after LVS (1.82 vs 1.23mg/dL; 1.71 vs 1.22mg/dL). The readmission rate at 30 days and 6 months was 7.4% and 36.0%, respectively. We did not find any significant predictors for 30-day readmission. Factors associated with higher readmission rate at 6 months (p <0.05) were: pre-infusion NYHA IV class (71% vs 30%), decompensated chronic HF (44% vs 9%) and atrial fibrillation or atrial flutter rhythm (56% vs 26%). In 27 cases, pre and post treatment NT-proBNP values were available. LVS therapy significantly reduced NT-proBNP from 10467 ± 8984 ng/L to 8237 ± 9500 ng/L (p=0.012) and improvement was observed in 93% of patients. Survival at 30 days and 6 months can be predicted by percentage of NT-proBNP improvement (-84.4% vs -28.4%, p=0.047; -92.3% vs -16.3%; p=0.012). Conclusion: AHF patients requiring inotropic therapy have high mortality and readmission rates. Several clinical features and analytical responses to LVS perfusion are predictors of these events. LVS significantly reduces NT-proBNP. The magnitude of this reduction is a predictor of short- and long-term mortality.